The Role of the Community in Community-Based Education - Jimi Kurniawan; Roni Rahman; Cecep Hilman (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2023)
The spirit of decentralization of education needs to be welcomed by educational institutions where educational institutions are given the freedom to manage their institutions according to the needs of the surrounding community and involve community participation in carrying out the educational process. To realize this, of course, various fields in the organizational structure of school institutions are maximally functioning, not only those that are academic in nature, but also those that are supportive, in this case the field of public relations, which is a mediator of communication between educational institutions and the community. This is what educational institutions and society have not realized where they still consider the two parts to be separate so that there is no concern for each other's existence, even though they are two groups that cannot be separated in the implementation of the educational process to produce moral generations of a moral society. The method used is literature review research. In the literature review, the author studies and understands theories related to the material and conducts studies and discussions with colleagues in finding solutions to the problems that the author encounters. In the discussion of this article, the author describes the problems regarding the new trend of future education based on the concept of the future curriculum, preparation for future education, and the essence of future education.